Peranan Skor SOFA dan Prokalsitonin dalam Memprediksi Luaran Mortalitas Sepsis di ICU: Sebuah Tinjauan Naratif - Catherina, Felicia; Syahrul, Muhammad Zulfadli; Rustam, Erlina (Fakultas Kedokteran, Universitas Andalas, 2025)
Background: Sepsis is a dysregulated host response to infection that leads to life-threatening organ dysfunction. SOFA score is used to assess the degree of organ dysfunction and is currently used in the latest sepsis definition. PCT is a biomarker which increases in inflammation and sepsis. Objective: to analyze the role of SOFA score and procalcitonin in predicting sepsis mortality outcome in ICU. Methods: Literature review discusses primary literature searched through PubMed and ScienceDirect databases, selected based on predetermined inclusion and exclusion criteria. Results: A total of 15 articles were included in this review. In studies evaluated a single SOFA score were found that the mean/median SOFA score in non-survivors were significantly higher than in survivors. In studies evaluated SOFA score data serially also showed the ability of SOFA score to predict mortality outcomes. One-time PCT measurements were performed in 93% studies in this review. The results obtained were that the mean/median initial PCT levels measured at admission or after sepsis diagnosis in non-survivors were higher than in survivors in 13 studies, but statistically significant differences were only found in 5 studies. Serial PCT measurements were only measured in 1 study, it found changes in PCT values on ICU admission and fifth day are significantly related to mortality. Conclusion: SOFA score is a good parameter for predicting sepsis mortality outcome in ICU, and in general, one-time PCT measurements do not play a significant role in predicting sepsis mortality outcome in ICU.